Immigration and American History : Essays in Honor of Theodore C. Blegen - Commager, Henry Steele (Book collections on Project MUSE., 1961)
Ten scholars noted for their studies in immigration history contribute essays to this volume. Dr. Commager, professor of history and American studies at Amherst College, surveys the course of immigration studies over the years. Oscar Handlin, director o.